Analysis of the Level of Critical Thinking Ability in Solving Story Problems in Economics Subjects at MA Muhammadiyah Pekanbaru - Frida Jasni Wibawanti; Suarman Suarman; RR Sri Kartikowati (Journal of Education Technology Information Social Sciences and Health, 2024)
This research aims to determine the critical thinking abilities of Class X IPS and XI IPS students in solving story problems in the Economics subject.  The research method used is a qualitative research method.  The subjects in this study were students of class X IPS S, totaling 13 students and XI IPS, totaling 27 students.  The type of data collected is in the form of qualitative data, namely the results of tests of students' critical thinking skills and the results of interviews.  Data was analyzed based on indicators.  The results of data analysis show that not all students have the critical thinking category, only students in the high category are able to solve critical thinking questions.  Meanwhile, students in the medium and low categories do not yet have actual critical thinking skills in terms of making further explanations and providing conclusions.  Keywords: Analysis, Critical Thinking Ability.